(untitled) (One Health & Risk Management, 2023)
When we look at the origin of all epidemics that are followed as a public health threat today, it is seen that human-environment interaction plays a major role. When epidemics such as pandemic influenza, avian influenza, Mers CoV, zikavirus, ebola, and COVID-19 in our world are examined, it is seen that they are of zoonotic origin or spread through vectors.